IMPLEMENTASI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS BERBASIS TEKNOLOGI INFORMASI PADA PERKULIAHAN KAJIAN MODE - Sri Widarwati (MAJALAH ILMIAH PEMBELAJARAN, 2007)
This research aims to know the quality improvement of mode lecturing study through instructional model of Teams Games Tournaments based on information technology at students of Teknik Busana of FT UNY.The type of this research is class action research. Research subject is 20 students of Teknik Busana who is studying Mode Lecturing. Research instrument applied is observation sheet. Instrument validity applied is construct validity and its reliability with test between observers. Research implementation refers to steps of Kemmis and Mac Taggart model with planning, action, and reflection cycles. This action research had done in four cycles. Data analytical technique applied is descriptive statistical analysis.Result of research shows the study implementation of Mode Learning by applying study model of Teams Games Tournaments which has been done is able to increase the lecturing quality, which can be seen from students learning enthusiasm and motivation, especially when discuss the information resulted by browsing the internet and exercises making. Applying of study model of Teams Games Tournaments can increase creativity and grow willingness of students to be creative in making works. It is proven by the increasing of average yielded and Pre test of 25 means not good becomes 28 at cycle I means good enough but at lower bound, average at cycle II is 32 means good enough, close to the highest bound at division of assessment category. Cycle III shows the improvement of average 40 is good and cycle IV with average of 45 that is proven with 80% of respondent designs at good category. Based on the result, one of efforts which can be done to increase quality of lecturing practically can apply the study model.This research aims to know the quality improvement of mode lecturing study through instructional model of Teams Games Tournaments based on information technology at students of Teknik Busana of FT UNY.The type of this research is class action research. Research subject is 20 students of Teknik Busana who is studying Mode Lecturing. Research instrument applied is observation sheet. Instrument validity applied is construct validity and its reliability with test between observers. Research implementation refers to steps of Kemmis and Mac Taggart model with planning, action, and reflection cycles. This action research had done in four cycles. Data analytical technique applied is descriptive statistical analysis.Result of research shows the study implementation of Mode Learning by applying study model of Teams Games Tournaments which has been done is able to increase the lecturing quality, which can be seen from students learning enthusiasm and motivation, especially when discuss the information resulted by browsing the internet and exercises making. Applying of study model of Teams Games Tournaments can increase creativity and grow willingness of students to be creative in making works. It is proven by the increasing of average yielded and Pre test of 25 means not good becomes 28 at cycle I means good enough but at lower bound, average at cycle II is 32 means good enough, close to the highest bound at division of assessment category. Cycle III shows the improvement of average 40 is good and cycle IV with average of 45 that is proven with 80% of respondent designs at good category. Based on the result, one of efforts which can be done to increase quality of lecturing practically can apply the study model.